Efektivitas Penggunaan Canva sebagai Media Pembelajaran Digital Interaktif: Sintesis Empiris terhadap Keterlibatan dan Hasil Belajar Siswa - Farmida, Andi Rika; Maulidya, Rahma; Nabilla, Fira; Efimayanti, Weny; Mahfuza, Nurul (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
Digital transformation in education has encouraged the integration of technology-based learning media to enhance instructional quality. One of the most widely used platforms is Canva, a web-based design application that provides various interactive visual features to support learning activities. This study aims to analyze trends in Canva utilization and identify its impact on student engagement and learning outcomes, particularly within Islamic Religious Education (IRE). A Systematic Literature Review (SLR) approach was employed using the PRISMA framework. Data were collected from articles published between 2020 and 2025 indexed in Google Scholar, DOAJ, Dimensions, and Scopus databases. Following identification, screening, and eligibility assessment processes, relevant studies were selected for in-depth analysis. The findings indicate that Canva positively contributes to student motivation, engagement, creativity, collaboration, digital literacy, and academic achievement. Within the context of Islamic Religious Education, Canva facilitates more engaging, contextualized, and interactive learning experiences that support student-centered instruction. However, the effectiveness of Canva is influenced by teachers’ digital competencies, technological infrastructure, and instructional design quality. This study recommends Canva as a relevant digital learning medium to support innovation in Islamic Religious Education in the era of educational digital transformation.